An investigation of the structure and role of English as a Foreign Language self-efficacy beliefs in the workplace. (July 2020) - Chauvin, Rachel; Fenouillet, Fabien; Scott Brewer, Stephen
Abstract: This study investigated the structure and role of the perceived English self-efficacy of French-speaking employees working in the health industry. Communicative competence in English as a Foreign Language is typically broken down into four language skills: reading, writing, listening and speaking. People may make use of one or more of these skills in their daily working lives, such as when they listen and speak during conversations. A professional English self-efficacy questionnaire (PESEQ) was developed in order to understand if and how EFL self-efficacy beliefs emerged in the organizational context as distinct psychological factors in connection with the four language skills. The scale was validated with 543 participants from the same organization. The exploratory and confirmatory factor analyses lead to the identification of three dimensions linked to a general self-efficacy factor: media understanding, receptive and productive written communication (reading and writing), receptive and productive oral communication (listening and speaking). A causal path model highlighted the indirect effect of pre-training professional English self-efficacy to on-the-job transfer, through its influence on motivation to learn, post-training performance self-efficacy and motivation to transfer. The discussion section addresses limitations and perspectives for research and teaching practices.